2011
DOI: 10.1269/jrr.11017
|View full text |Cite
|
Sign up to set email alerts
|

Screening for 137Cs Body Burden Due to the Chernobyl Accident in Korosten City, Zhitomir, Ukraine: 1996–2008

Abstract: During the Chernobyl Nuclear Power Plant (CNPP) accident on 26 April 1986, large amounts of radionuclides were released and spread to vast areas. Inhabitants residing around CNPP have been exposed to external and internal irradiation due to the long half-life of (137)Cs (30 years). In this study, we screened for internal whole-body (137)Cs concentration using a whole-body counter in the Zhitomir state of Ukraine. The total number of participants was 144,972 (96,149 females and 48,823 males). The median body bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…WBC results for the residents of Korosten City, Ukraine were reported as 37.2 kBq/kg [12] 10 years after the 1996 Chernobyl nuclear power plant disaster. On comparing the results obtained from the Namie residents with the residents of Korosten City, it was observed that radioactivity was much lower than that of Korosten City considering our values are systemic whole body values.…”
Section: Discussionmentioning
confidence: 99%
“…WBC results for the residents of Korosten City, Ukraine were reported as 37.2 kBq/kg [12] 10 years after the 1996 Chernobyl nuclear power plant disaster. On comparing the results obtained from the Namie residents with the residents of Korosten City, it was observed that radioactivity was much lower than that of Korosten City considering our values are systemic whole body values.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the experiences of the Chernobyl Nuclear Power Plant (CNPP) accident in 1986, it is known that internal radiation exposure due to 131 I in the thyroid gland causes an increased risk of childhood thyroid cancer [5] . On March 17, 2011, the Director General of the Nuclear Emergency Response Headquarters of Japan initiated food control measures to minimize internal radiation exposure to 131 I, and disposed of all contaminated raw milk.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of 134 Cs and 137 Cs in the human body is non-specific, except for weak accumulation in muscle and bone [5] , [6] , and its biological half-life in adults is about 70 days [7] . Internal radiation doses are determined using whole body counters (WBC), which are special instruments usually housed within or around nuclear facilities [8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioactive cesium was highly contaminated among animals and plants in the forest as the cycle of the food chain was polluted with it. High levels of 137 Cs were detected in mushrooms, grapes, and meat 20 y after the accident, and internal exposure continues through ingestion in parts of Belarus, Ukraine, and Russia (Hayashida et al 2011).…”
Section: Lessons Learned From the Chernobyl Nuclear Reactor Accidentmentioning
confidence: 99%